Anterior Inferior Iliac Spine (AIIS) and Subspine Hip Impingement - Patrick Carton; David Filan (2019)
Background: Abnormal morphology of the anterior inferior iliac spine (AIIS) and the subspine region of the acetabular rim are increasingly being recognised as a source of symptomatic extra-articular hip impingement.This review article aims to highlight important differences in the pathogenesis, clinical presentation and management of extra-articular hip impingement from both the AI-IS and subspine bony regions, and the outcome following surgical intervention.Methods: A literature review was undertaken to examine the supporting evidence for AIIS and subspine hip impingement.A narrative account of the Author's professional experience in this area, including operative technique for arthroscopic correction, is also presented.Results: Abnormal morphology of the AIIS and subspine region has been classified using cadaveric, radiological and arthroscopic means; the clinical presentation and operative treatment has been documented in several case series studies.Dual pathology is often present -recognition and treatment of both intra-and extra-articular components are necessary for good postoperative outcome.Conclusions: AIIS and sub-spine hip impingement should be considered as distinct pathological entities, which may also co-exist.Symptom relief can be expected following arthroscopic deformity correction with the treatment of concomitant intra-articular pathology.Failure to recognise and treat the extra-articular component may affect postoperative outcome.Level of evidence: V.